Clinical profile of different type of tuberculosis in hospitalized children in tertiary care center - Thanvi, Rashmi S; Jain, Ashish; Patel, Shital M; Patel, Nehal H; Gunjana, Geet; Patel, Krina (Indian Journal of Child Health, 2017)
Background: Since the implementation of directly observed treatment short (DOTS) program, the prevalence, clinical profile, and risk factors of pulmonary and non-pulmonary tuberculosis (TB) necessitating hospitalization in pediatric patients are not evaluated extensively. Materials and Methods: We designed a prospective observational study to evaluate the clinical profile of different types of TB in hospitalized children <12 years old. Different types of TB in children hospitalized from 1st January 2013 to 30th June 2014 were recorded. Detailed clinical history, clinical examination findings, diagnostic methods, and treatment of these cases were analyzed by age groups and types of TB. Results: During the study period, 150 (2.8% of total admission) patients with TB were admitted in our institute. 87 (58%) patients were <5 years old, and 92 (61.33%) children were male. 140 (93.33%) children were malnourished. The clinical profile of TB included neuro TB in 78 (37.32%), pulmonary in 67 (32.05), abdominal in 27 (12.91%), and disseminated in 27 (12.91%) patients. Less than half of children with neuro TB and disseminated TB were immunized with Bacillus calmette-guerin (BCG). Conclusion: Despite aggressive DOTS implementation, the prevalence of TB, particularly, non-pulmonary TB in children is quite alarming. All the variants of TB are prevalent in the children. The neuro TB and the pulmonary TB dominate in the hospitalized cases. Younger age, lack of protection of BCG vaccination, and malnutrition are the main risk factors in childhood TB.